INTERNALISASI NILAI PENDIDKAN ISLAM MELALUI TRADISI MALAM ELA-ELA DALAM PENGUATAN PEMAHAMAN KEAGAMAAN MASYARAAKT KAMPUNG WAIGAMA DISTRIK MISOOL UTARA - Buatan, Mustafa Musa; Nur, Indria (Pascasarjana IAIN Sorong, 2024)
The objectives of this study are: (1) To analyze the process of the Ela-Ela night tradition in strengthening the religious understanding of the Waigama Village community. (2) To analyze the internalization of Islamic educational values through the Ela-Ela night tradition in strengthening the religious understanding of the Waigama Village community. (3) To analyze the impact of the internalization of Islamic educational values through this tradition. This study is a qualitative field research using a phenomenological approach. Data collection techniques were conducted through observation, interviews, and documentation. The research was carried out over four months involving syara' judges, religious leaders, traditional leaders, community leaders, educational figures, female figures, and the residents of Waigama Village as informants. The study found that the Ela-Ela night tradition in Waigama Village consists of three stages: (1) preparation, implementation, and closing. (2) The educational values and Islamic religious understanding within this tradition include (a) aqidah values, (b) shariah, and (c) akhlak. (3) The impact of the internalization of educational values through this tradition includes cultivating the community's habit of reciting the Qur'an, performing dhikr and prayers, as well as strengthening social bonds and cooperation.